2019
DOI: 10.1108/ajim-06-2018-0150
|View full text |Cite
|
Sign up to set email alerts
|

Relation between internet financial information disclosure and internal control in Spanish local governments

Abstract: Purpose The application of new public governance by many countries has led to the creation of new management systems in public administration and the development of an effective accounting structure with efficient internal control to guarantee a proper provision of services that meet citizens’ requirements. The purpose of this paper is to focus on Spanish local government with the intention of determining the impact of the internal control structure on the disclosure of financial information on the internet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
2
15
1
Order By: Relevance
“…Adi et al (2016) have analysed the disclosure of management performance in the Government of Indonesia and showed that the published information disclosed only 35.46% of the required information. Moreno-Enguix et al (2019) have observed that 43.5% of Spanish municipalities do not disclose the financial information required by law. The conclusion is explained by the recent establishment of new accounting standards in the public sector.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Adi et al (2016) have analysed the disclosure of management performance in the Government of Indonesia and showed that the published information disclosed only 35.46% of the required information. Moreno-Enguix et al (2019) have observed that 43.5% of Spanish municipalities do not disclose the financial information required by law. The conclusion is explained by the recent establishment of new accounting standards in the public sector.…”
Section: Resultsmentioning
confidence: 99%
“…Martani and Lestiani (2012) argue that the increasing size of the local government will make the voters concerned about its performance. Researchers (Garcia and Garcia-Garcia 2010;Ali and Saidin 2016;Moreno-Enguix et al 2019) agree that the size of the organisation in the public sector is considered as one of the determining variables of accounting practices and characteristics of financial disclosure, which is based on different theories. For instance, following the positive accounting theory, Falkman and Tagesson (2008) have claimed that size should influence the political pressure that municipalities experience to comply with accounting standards.…”
Section: Size Of Municipalitymentioning
confidence: 99%
See 3 more Smart Citations